1994
DOI: 10.1073/pnas.91.4.1248
|View full text |Cite
|
Sign up to set email alerts
|

Impact melting of frozen oceans on the early Earth: Implications for the origin of life

Abstract: Without sufficient greenhouse gases in the atmosphere, the early Earth would have become a permanently frozen planet because the young Sun was less luminous than it is today. Several resolutions to this faint young Sun-frozen Earth paradox have been proposed, with an atmosphere rich in CO2 being the one generally favored. However, these models assume that there were no mechanisms for melting a once frozen ocean. Here we show that bolide impacts between about 3.6 and 4.0 billion years ago could have episodicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 30 publications
1
79
0
Order By: Relevance
“…Attractive environments for such scenarios are in particular hotsprings and geysers, in which freezing and thawing occurs in close proximity and a huge variety of temperature gradients exist. In any case, ice matrices have been abundantly available throughout history, with several theories implying that the Earth's surface might have been largely frozen several times (27,28). Interestingly, the plausibility of ice as a matrix has also been discussed with respect to other aspects about the origin of metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Attractive environments for such scenarios are in particular hotsprings and geysers, in which freezing and thawing occurs in close proximity and a huge variety of temperature gradients exist. In any case, ice matrices have been abundantly available throughout history, with several theories implying that the Earth's surface might have been largely frozen several times (27,28). Interestingly, the plausibility of ice as a matrix has also been discussed with respect to other aspects about the origin of metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Some atmospheric models incorporate high partial pressures of CO2 to raise the temperature of the Earth by a greenhouse effect and thus prevent the complete freezing of the oceans (Kasting 1993). However, a frozen Earth has some advantages for prebiotic chemistry (Bada et al 1994). But again, there is no direct evidence either way.…”
Section: What Was the Physical Setting Of The Origin Of Life?mentioning
confidence: 99%
“…Other sites for the origin of life have since been proposed, ranging from transient melt zones in a global ice pack (Bada et al 1994) to hydrothermal vents (Corliss et al 1981;Baross & Hoffman 1983) and to subterranean lithic zones (Pace 1991). Many such sites contain microbial populations that are extremophiles, and it has been suggested that the last universal common ancestor lived in a deep hydrothermal site secure from sterilizing giant impacts (Sleep et al 1989).…”
Section: The Physical Environment and The Origin Of Lifementioning
confidence: 99%